'Genetic loading' or 'evil mind': current conceptions of depression in Myanmar from the perspective of healthcare professionals. (7th August 2018) - Schödwell, Steffen; Steinhäuser, Theresa; Auckenthaler, Anna
Abstract : In Myanmar, a country that has just recently opened up to the international community, Buddhist and traditional healing methods are still widely applied to various diseases and conditions. The aim of this study was to ascertain how professionals from the biomedical healthcare system in Myanmar experience interactions with patients with depression, based on the professionals' conceptualisation of this disorder. Six problem-centred interviews were conducted and analysed with grounded theory methodology. The interviewed professionals conceptualised three ways of understanding depression, including different treatment strategies: a biomedical, a contextual and a Buddhist concept of depression. Concerning the patients' perspective, the professionals mentioned somatic, religious and supernatural explanatory models, as well as corresponding help-seeking behaviour. Our results suggest that by taking a biomedical approach, professionals risk neglecting both the needs and resources of Myanmar patients with depressive symptoms.